SOME USEFUL POINTS ABOUTE CREDIT-MODULE SYSTEM IN HIGH SCHOOLS - Nazarova Sayyora Azimjanovna (Journal of Higher Education and Academic Advancement, 2024)
The purpose of the Decree of the President of the Republic of Uzbekistan dated in October 8, 2019 «On approval of the Concept of development of higher education in the Republic of Uzbekistan until 2030» PF-5847 : improving the quality and efficiency of higher education, coordination of education A number of measures have been identified to improve educational attainment levels on the basis of educational standards and to gradually transfer the educational process of higher education institutions to a credit